Hubungan Status Gizi dengan Lama Menstruasi pada Remaja Putri di Kota Yogyakarta - Bima Suryantara; Gunarmi Gunarmi; Eka Vicky Yulivantina (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2022)
ABSTRACTDuring adolescence, nutritional needs need special attention because during adolescence there is a physiological growth and development of organs. Growth in adolescence affects the needs, absorption, and use of nutrients, this is accompanied by rapid enlargement of organs and body tissues. Hormonal changes during adolescence also cause many physiological changes that affect nutritional needs in adolescents. Nutritional status affects menstruation mainly through the provision of materials to make the endometrial lining again and its effect on female hormone levels. The purpose of this study was to determine the relationship between nutritional status and duration of menstruation in adolescent girls. This study uses a quantitative correlation method with a cross sectional time approach. Sampling with total sampling technique with a sample of 62 young women. The results of the analysis using the chi square test showed that there was no relationship between nutritional status and the length of menstruation in adolescent girls in the city of Yogyakarta, which was indicated by the p value = 0.831.Keywords: nutritional status, duration of menstruation.